Implementasi Konsep Kerja Sama Internasional Dalam Edukasi Anti Korupsi - Meganingratna, Andi (JUPE : Jurnal Pendidikan Mandala, 2023)
As a global phenomenon, corruption is something that plagues almost all countries and its negative impact can specifically affect the growth of a country. This corruption cannot be dealt with by relying solely on domestic efforts. One way to do this is through anti-corruption education through international cooperation. This research aims to see how the implementation of international cooperation in educating people and countries about the importance of anti-corruption initiatives globally. Using the concept of international cooperation, it is found that many international organizations have incorporated the importance of anti-corruption education into their programs. This education is carried out through cooperation so that the results can be more evenly distributed among member countries. International cooperation ensures procedures in reducing corruption and promoting increased public integrity.